Characterization of Microbiota in Cancerous Lung and the Contralateral Non-Cancerous Lung Within Lung Cancer Patients - Zhuo, Minglei; An, Tongtong; Zhang, Chaoting; Wang, Ziping (Frontiers in Oncology, 2020)
Background: The functional role of lung microbiota has attracted an accumulating attention recently, but the profile and functional role of the lung microbiome in patients with lung cancer remained largely unknown. Methods: To evaluate the association of the microbiota with lung cancer, we performed comparative analysis of the lung microbiome using 16S rRNA amplicon sequencing approach in the paired bronchoalveolar lavage fluid samples (paired samples from cancerous lung and the contralateral noncancerous lung) from 50 cancer patients with unilateral lobar masses. Results: We found relative abundance of phylum Tenericutes, its class Mollicutes, its order Entomoplasmatales, its family Spiroplasmataceae, and its genus Spiroplasma were significantly increased in cancerous lung, but decreased relative abundance of phylum Bacteroidetes, its class Bacteroidia, and its order Bacteroidales were significantly decreased in cancerous lung. In addition, relative abundance of family Leuconostocaceae and its genus Weissella were significantly increased in cancerous lung. Conclusions: Our findings provide insights into a change of lung microbiome community associated with the development of lung cancer.